Self-reported ongoing adherence to diet is associated with lower depression, fatigue, and disability, in people with multiple sclerosis - Yu, Maggie; Jelinek, George; Simpson-Yap, Steve; Neate, Sandra; Nag, Nupur (Frontiers in Nutrition, 2023)
Introduction Increasingly, dietary improvements have been shown to have positive associations with health outcomes in people with multiple sclerosis (pwMS). However, adhering to a MS-specific or high-quality diet may be a challenge. We therefore assessed the level of diet-adherence necessary to improve health outcomes of depression, fatigue, and disability. Methods Data from an international population of pwMS followed over 7.5 years (n = 671) were analyzed. Self-reported diet quality via diet habits questionnaire (DHQ), and adherence to six MS-diets [Ashton Embry Best Bet, McDougall, Overcoming MS (OMS), Paleolithic (Paleo), Swank, and Wahls] were queried at two timepoints. Four levels of diet adherence were assessed: non-adherence at either timepoint; ceased at second timepoint; commenced at second timepoint; and ongoing at both timepoints. Associations between adherence to OMS and high-quality diet (DHQ score > median) with depression, fatigue, and disability, were assessed by log-binomial regression models adjusted for confounders. Results Forty-two percent of pwMS reported ongoing-adherence to a MS-diet at both timepoints, OMS (33%), Swank (4%), Wahls (1.5%), other (<1%). Of these, only OMS-diet adherence was analyzed for associations due to data availability. Ongoing-adherence to the OMS-diet or a high-quality diet, was associated with lower depression compared to non-adherence [OMS: Risk ratios (RR) = 0.80, p = 0.021; DHQ: RR = 0.78, p = 0.009] and ceased-adherence (OMS: RR = 0.70, p = 0.008; DHQ: RR = 0.70, p = 0.010), respectively. Ongoing-adherence to OMS-diet was associated with lower fatigue (RR = 0.71, p = 0.031) and lower severe disability (RR = 0.43, p = 0.033) compared to ceased-adherence. Conclusion Results suggest potential benefits of adherence to the OMS- or a high-quality diet on MS health outcomes, with ongoing-adherence likely best. Diet modification and maintenance may serve as a point of intervention to manage MS symptoms, especially depression, in pwMS.